Aplicação e avaliação de critérios semi-empíricos para o desenvolvimento de novas ligas vítreas do sistema Ti-Cu-Ni - Mendes, Marcio Andreato Batista (Universidade Federal de São Carlos, 2013)
The selection of good glass forming compositions is not a simple undertaking and many groups work on models and theoretical approximations in order to predict or at least guide the laborious and expensive experimental pinpointing of compositions in a given system. The DEMa-UFSCar group , in partnership with the solidification group of the EESC/SMM-USP , have worked in semi-empirical criteria based on a combination of topological aspects (criterion λmin), electronegativity (criteria Δe) and enthalpy of mixing of the elements [criterion Log(RC)] to predict compositions with high Glass Forming Ability (GFA). These criteria have shown good results to predict compositions with high GFA. The aim of this thesis was to contribute to the efforts being made to improve the efficiency and to expand the applications of these proposed criteria. For this study, we used the Log (RC) criterion and the combined criteria λmin x Δe. Using these criteria, nine composition of the Ti-Cu-Ni system were selected and were processed in the laboratory, so the theoretical and experimental results were compared. The experimental results were also compared with the theoretical results of other criteria reported in the literature. This study was performed with the use of rapidly solidified ribbons and analyzed by thermal analysis (DSC), Xray diffraction (XRD) and statistical tools. The results showed that the proposed criteria have low correlation with the experimental results; and to increase that correlation we proposed some improvements in the criteria. Additionally, through another study it was possible to determine the first stages of devitrification of the amorphous structure and to compare them with the predictions of the criteria Log (RC) and λmin x Δe. For this, we selected 4 alloys of the Ti-Cu-Ni system and a study of crystallization kinetics was performed using transmission electron microscopy (TEM), DSC and XRD analyzes. It was revealed that the experimental results are consistent with the theoretical results partially.
Application and evaluation of semi-empirical criteria in the development of new amorphous Ti-Ni-Cu alloys
Keywords: Metalurgia; Metais amorfos; Solidificação rápida; Amorfização; Análise cinética de reações; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA